PENERAPAN KONSEP SUNK COST TERHADAP KEPUTUSAN PENGGANTIAN MESIN FOTOKOPI PADA TOKO GIRSA - Sirang, Andrea Giovani; Saerang, David Paul Elia; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
Many methods of costs incurred to assist managers in making decisions. One of the so-called sunk costs, Sunk costs are costs incurred in the past and can not be changed now and in the future. Sunk costs often affect a company manager's decision to take the right decision. One was the decision in terms of financing fixed assets owned by the company. This research was conducted at Toko Girsa which is located in R.W. Monginsidi Road 49, Manado. The object of this is enelitian fixed assets such as machinery fotocopy Canon IR 6070 owned company. The purpose of this study was to determine the application of the concept of sunk costs and influence in decision making purchases of fixed assets at Toko Girsa. The method used in this research is descriptive method is a method that collects, formulate and classify and interpret the data obtained by the analysis of quantitative data presented in the form of numbers that are related to sunk costs arising from the financing of fixed assets. The results showed that the sunk costs can not be used as a basis for making the right decisions for the management, including fixed asset purchase decision.